Primary Esophageal Extra-Gonadal Yolk Sac Tumor Metastasized to the Liver (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF To see the formatted meeting abstract.
Keywords: Internal Medicine; Case Report